2006
DOI: 10.1182/blood.v108.11.437.437
|View full text |Cite
|
Sign up to set email alerts
|

Donor Natural Killer Cell Allorecognition of Missing Self in Haploidentical Hematopoietic Transplantation for Acute Myeloid Leukemia: Challenging Its Predictive Value.

Abstract: In haploidentical transplants that are KIR ligand mismatched in the GvH direction, functional donor NK-cells that express as their sole inhibitory receptor for self, a KIR for the HLA-class-I group which is absent in the recipient, sense the missing expression of the self class-I ligand on allogeneic targets and mediate alloreactions. In a limited series of transplants donor-vs-recipient NK-cell alloreactivity reduced the risk of AML relapse and markedly improved EFS (Ruggeri L, Science 2002). Here, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
168
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(179 citation statements)
references
References 0 publications
6
168
5
Order By: Relevance
“…The rationale for using DLI in these trials is derived from the strong GvL responses seen after DLI [62], and the rationale for using adoptive transfer of NK cells is derived from the known sensitivity of neuroblastoma cells to NK cell Cytotoxicity [20][21][22]. Along the same line, haploidentical HSCT is considered of particular interest because of the reported association of strong alloreactive NK cell-mediated GvL responses observed in hematological malignancies [67,[82][83][84][85]. As reviewed by others [86], a KIR-ligand mismatch in the graft-versus-host direction in a donor and transplant recipient pair has been found in several studies to be predictive for a low risk of relapse [67,[82][83][84][85].…”
Section: Allogeneic Hematopoietic Stem Cell Transplantation and The Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for using DLI in these trials is derived from the strong GvL responses seen after DLI [62], and the rationale for using adoptive transfer of NK cells is derived from the known sensitivity of neuroblastoma cells to NK cell Cytotoxicity [20][21][22]. Along the same line, haploidentical HSCT is considered of particular interest because of the reported association of strong alloreactive NK cell-mediated GvL responses observed in hematological malignancies [67,[82][83][84][85]. As reviewed by others [86], a KIR-ligand mismatch in the graft-versus-host direction in a donor and transplant recipient pair has been found in several studies to be predictive for a low risk of relapse [67,[82][83][84][85].…”
Section: Allogeneic Hematopoietic Stem Cell Transplantation and The Gmentioning
confidence: 99%
“…Along the same line, haploidentical HSCT is considered of particular interest because of the reported association of strong alloreactive NK cell-mediated GvL responses observed in hematological malignancies [67,[82][83][84][85]. As reviewed by others [86], a KIR-ligand mismatch in the graft-versus-host direction in a donor and transplant recipient pair has been found in several studies to be predictive for a low risk of relapse [67,[82][83][84][85]. This is a form of anti-host NK cell alloreactivity that extends to the recipient tumor cell and that relies on the key principle of NK cell killing on the basis of missing-self.…”
Section: Allogeneic Hematopoietic Stem Cell Transplantation and The Gmentioning
confidence: 99%
“…In studies by Velardi's group alloreactive NK cells were detected for up to 1 year after transplantation [54]. Recent studies have confirmed and extended these findings.…”
Section: Origin Of Donor's Alloreactive Nk Cells In the Recipient Andmentioning
confidence: 81%
“…In the second category, all KIR expressed by NK cells recognized the HLA-class I alleles of the patient (lack of KIR/KIRligand mismatch). The presence of alloreactive NK cells has been found to positively correlate with the successful outcome of transplantation either in adults with acute myeloid leukemias (AML) [52,54] or in pediatric patients with high risk lymphoblastic leukemias (ALL) [48,55]. Although the presence of alloreactive NK cells can be predicted by the analysis of the KIR gene profile of the donor and by the HLA class I typing of both donor and recipient, the actual presence and size of the alloreactive cell NK subset can be assessed by cytofluorimetric analysis.…”
Section: Nk Alloreactivity In Haploidentical Hsctmentioning
confidence: 99%
“…For almost all leukemia patients who fail to find a matched donor, whether related or unrelated, or a suitable cord blood unit, transplantation from family donors who are matched for one HLA haplotype and fully mismatched at the HLA classes I and II loci of the unshared haplotype (haploidentical) is a viable option. Milestones along the way toward successful haploidentical transplantation were observations that: (1) extensive ex vivo T cell depletion of the graft prevented graft versus host disease (GvHD), in haploidentical transplants for patients with severe combined immunodeficiency; 25 (2) a "megadose" of T cell-depleted stem cells ensured engraftment across major histocompatibility complex (MHC) barriers in mice, 26 and across HLA barriers in clinical transplantation; [27][28][29][30][31] (3) human NK cells exerted alloreactivity; [32][33][34][35][36][37][38][39] (4) transplantation from haploidentical donors that were able to mount donor versus recipient NK cell alloreactions eradicated acute myeloid leukemia (AML), favored engraftment, protected from GvHD and greatly improved survival, as demonstrated by integrating clinical and preclinical data. [32][33][34][35][36][37][38][39] Current conditioning protocols include totalbody irradiation (TBI), fludarabine, thiotepa, and anti-T cell antibodies (anti-thymocyte globulin, ATG) 15,[28][29][30][31] (Fig.…”
Section: Introductionmentioning
confidence: 99%